Crystallinity and temperature dependent mechanical properties of Poly(4-methyl-1-pentene). (13th March 2023) - Han, Cenhui; Lyu, Dong; Lu, Ying; Men, Yongfeng
Abstract: Crystallinity and temperature dependent modulus in poly(4-methyl-1-pentene) were investigated over a wide temperature range covering glass transition of the amorphous phase. It turns out that the storage moduli of different samples decrease with the increase of crystallinity below Tg. The storage moduli of different samples are the same regardless of crystallinity at around 45 °C where the densities of crystalline and amorphous phases are identical. A model considering parallelly arranged crystalline skeleton and amorphous network allows a decomposition of the measured modulus into moduli of both phases. In addition to the fact that the modulus of amorphous phase in the glassy state is much larger than that of crystalline phase due to a higher density in amorphous phase than that of the crystals, a peculiar positive temperature dependent apparent crystalline phase modulus below Tg was observed. This seemingly anti-intuitive result can be understood by considering the strong constraint of the crystalline phase by the denser amorphous network at lower temperatures due to different thermal expansion coefficients of the two phases. Graphical abstract: Image 1 Highlights: The modulus of Poly(4-methyl-1-pentene) decreases with the increase of crystallinity below Tg. Higher modulus of amorphous phase below Tg due to higher density than that of the crystalline phase. Crystalline phase modulus increase with T below Tg due to constraints imposed by amorphous phase.